2012
DOI: 10.1111/1365-2664.12010
|View full text |Cite
|
Sign up to set email alerts
|

Non‐random extinctions dominate plant community changes in abandoned coppices

Abstract: Summary1. The plant community structure of European lowland forests has changed dramatically in the twentieth century, leading to biodiversity decline at various spatial scales. However, due to methodological difficulties associated with simultaneous changes in species diversity and composition, ecological processes behind the changes are still poorly understood. 2. We analysed temporal changes in forest plant community after the mid-twentieth-century abandonment of coppicing in a typical Central European fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 55 publications
6
109
0
4
Order By: Relevance
“…Besides leading to a convergence in forest structure, the high forest strategy, much as coppice abandonment, might lead to a dominance, at the landscape level, of senescent woodlands and the loss of the earlier successional stages of forest ecosystems. Heterogeneity of forest stand development stages, including coppice woodlands, at different ecosystem organisation levels, has been advocated for many years in connection with the maintenance of high levels of beta-diversity (Hunter 1990, Buckley 1992, Fuller & Warren 1993, Mairota et al 2006, Chiarucci et al 2008, Garadnai et al 2010, Kopecký et al 2013, Buckley & Mills 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Besides leading to a convergence in forest structure, the high forest strategy, much as coppice abandonment, might lead to a dominance, at the landscape level, of senescent woodlands and the loss of the earlier successional stages of forest ecosystems. Heterogeneity of forest stand development stages, including coppice woodlands, at different ecosystem organisation levels, has been advocated for many years in connection with the maintenance of high levels of beta-diversity (Hunter 1990, Buckley 1992, Fuller & Warren 1993, Mairota et al 2006, Chiarucci et al 2008, Garadnai et al 2010, Kopecký et al 2013, Buckley & Mills 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Coppices were used as a wood source until the second half of the 19 th century (Peterken 1993). Since then, coppices have practically disappeared (Kopecký et al 2013) because of gradual conversion of low forests to high forests, especially in central and northwestern Europe (Matthews 1991;Peterken 1993). The main reason for forest conversion was increasing demand for timber of higher quality (Hédl et al 2010) and policy of nature conservation that considered the low forest system as undesirable at that time (Szabó 2010).…”
Section: Study Areamentioning
confidence: 99%
“…The main reason for forest conversion was increasing demand for timber of higher quality (Hédl et al 2010) and policy of nature conservation that considered the low forest system as undesirable at that time (Szabó 2010). On the contrary, the abandonment of this system can cause a reduction in species diversity (Spitzer et al 2008) because of structure homogenization that limits mainly light-demanding species (Kopecký et al 2013). Such a trend was proved by Vanhellemont et al (2014), who demonstrated a decrease in the representation of light-demanding species and an increase in maple (Acer platanoides L.) and hazel (Corylus avellana L.).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, since 1945, a decline in the share of the wild service tree in oak forests has been mainly caused by abandoning management with the use of the coppice-with-standard system (Szymura 2012). According to Kopecký et al (2013), cessation of coppicing in the 1900s has gradually lead to the extinction of many photophilous species representative for forest communities in Europe's lowlands.…”
Section: Introductionmentioning
confidence: 99%